A Visual Turn for Organizational Ethnography: Embodying the Subject in Video-Based Research - Hassard, John; Burns, Diane; Hyde, Paula; Burns, John-Paul (Organization studies, 2018)
For organizational ethnography we argue that traditional philosophies of onto-epistemological realism be supplanted by interpretive and reflexive thinking to provide fresh theoretical assumptions and new methodological proposals for film- and video-based research. The argument is developed in three phases: First, to establish analytical context, we explore the historical evolution of the ethnographic organizational documentary and discuss habitual problems – methodological, philosophical and technical – that filmmakers have faced when claiming qualities of directness and objectivity in their work, that is, through the style of ‘film-truth’. Second, to advance new conceptual logic for video-based organizational research, we supplant the objectivist and realist philosophy underpinning traditional documentary filmmaking with sociologically interpretive and reflexive arguments for undertaking ethnography in organizations, a subjective process which importantly yields greater understanding of affect and embodiment. Finally, to define new methodological opportunities, these interpretive and reflexive arguments are marshalled to underpin a strategy of participatory thinking in video-based organizational ethnography – a ‘withness’ approach facilitating a greater sense of affect and embodiment as well as polyvocal interpretation of visual data; a practice which sees filmmakers, social theorists, participants and viewers alike united in analytical space.